The stars of heaven - Pickover, Clifford A. (Oxford University Press, 2004)
Do a little armchair space travel, rub elbows with alien life forms, and stretch your mind to the furthest corners of our uncharted universe. With this astonishing guidebook, you don't have to be an astronomer to explore the mysteries of stars and their profound meaning for human existence. Clifford A. Pickover tackles a range of topics from stellar evolution to the fundamental reasons why the universe permits life to flourish. He alternates sections that explain the mysteries of the cosmos with sections that dramatize mind-expanding concepts through a fictional dialog between futuristic human.